2021
DOI: 10.1007/s12035-021-02649-7
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 Signaling Disrupts Social Behavior by Modulating Brain Volumetric Changes and Microglia Morphology

Abstract: Autism spectrum disorder (ASD) is a disease characterized by reduced social interaction and stereotypic behaviors and related to macroscopic volumetric changes in cerebellar and somatosensory cortices (SPP). Epidemiological and preclinical models have confirmed that a proinflammatory profile during fetal development increases ASD susceptibility after birth. Here, we aimed to globally identify the effect of maternal exposure to high-energy dense diets, which we refer to as cafeteria diet (CAF) on peripheral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Appreciating for the contribution of Michael V. Lombardo et al, who recruited a total of 188 toddles, including 81 individuals of ASD around 3-4 years [11], we found that the myeloid cells were statistically signi cant boosted and activated, particularly neutrophils (Fig. 2C-D) in the peripheral blood of autism patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Appreciating for the contribution of Michael V. Lombardo et al, who recruited a total of 188 toddles, including 81 individuals of ASD around 3-4 years [11], we found that the myeloid cells were statistically signi cant boosted and activated, particularly neutrophils (Fig. 2C-D) in the peripheral blood of autism patients.…”
Section: Discussionsupporting
confidence: 58%
“…Admittedly, ASD patients and ASD model rodent display immune dysfunction [7][8][9]. The vital pathways enriched in ammatory regulators such as interleukin-17A (IL-17A), interleukin-6 (IL-6) and MCP-1, were notably noticed presently [9][10][11]. The expression level of the ASD-risk genes co-expressed in the peripheral blood leukocytes and the brain tissues were proved associated with multivariate functional neuroimaging (fMRI) response to speech between typically developing toddlers and toddlers with ASD [12].…”
Section: Introductionmentioning
confidence: 99%
“…Using data collected by Michael V. Lombardo et al, who recruited a total of 188 toddlers, including 81 individuals with ASD at approximately 3-4 years of age [11], we found that myeloid cells were signi cantly boosted and activated, particularly neutrophils (Fig. 2C-D), in the peripheral blood of autism patients.…”
Section: Discussionmentioning
confidence: 82%
“…ASD patients and ASD model rodents display immune dysfunction [7][8][9]. Vital pathways enriched in in ammatory regulators, such as interleukin-17A (IL-17A), interleukin-6 (IL-6) and MCP-1, are notable [9][10][11]. The expression levels of ASD risk genes coexpressed in peripheral blood leukocytes and brain tissues were proven to be associated with multivariate functional neuroimaging (fMRI) response to speech between typically developing toddlers and toddlers with ASD [12].…”
Section: Introductionmentioning
confidence: 99%
“…Structural and functional alterations of primary somatosensory cortex have been reported to regulate social behavior, socio-emotional processing and affective functions in humans and preclinical animal models [33][34][35][36]. To investigate the cellular mechanism underlying abnormal behaviors in Wdr62 Nex-cKO mice, we analyzed pyramidal neuronal morphology by crossing Wdr62 Nex-cKO mice with Thy1-GFPm transgenic mice, which can express EGFP in sparse subsets of excitatory neurons [37].…”
Section: Wdr62 Regulates Neuronal Dendritic Complexity and Spine Dens...mentioning
confidence: 99%